Populations locales et unités de conservation : de l’exclusion à une inclusion incomplète (le cas de la Forêt nationale du Tapajós, Amazonie brésilienne) - Claire Couly; Xavier Arnauld de Sartre (Confins)
The increasing importance accorded to protected areas (PAs) in international nature conservation policies calls for in-depth studies into the role given to local populations living within these areas. Even if local populations are often excluded from the PA management process, their inclusion is also possible. It is what we show in this paper, basing ourselves on a PA case study in the Brazilian Amazon and focusing specifically on the development of this inclusion, its modalities and on the remaining problems to be resolved. The historical analysis of the conflict in the Tapajós national Forest shows that PA categories in Brazil have managed to adapt themselves to local contexts. The implementation of this PA, and its subsequent acceptance by local populations, has thus required policy makers to adapt to local resource use and management practices, yet has also necessitated that local populations conform to institutional management norms. Furthemore, the inclusion of local populations in PA governance has been partly promoted by international institutions, in order to benefit from their financial support at local scale for different development programs. Since, the relationship between local populations and policy makers have been stabilized in this PA, and the challenges in maintaining inhabitants on this territory have now shifted towards their strong dependence on the resources and consumer products from the city and the transformations induced by development projects in local production systems.